Oscillations Governed by the Incoherent Dynamics in Necroptotic Signaling - Xu, Fei; Yin, Zhiyong; Zhu, Ligang; Jin, Jun; He, Qingzhu; Li, Xiang; Shuai, Jianwei (Frontiers in Physics, 2021)
Emerging evidences have suggested that oscillation is important for the induction of cell death. However, whether and how oscillation behavior is involved and required for necroptosis remain elusive. To address this question, a minimal necroptotic circuit is proposed based on the CNS pathway. Stochastic parameter analysis demonstrates that the essential structure for oscillation of the CNS circuit is constituted by a paradoxical component embedded with positive feedback among the three protein nodes, i.e., RIP1, caspase-8, and RIP3. Distribution characteristics of all parameters in the CNS circuit with stable oscillation are investigated as well, and a unidirectional bias with fast and slow dynamics that are required for high occurrence probability of oscillation is identified. Four types of oscillation behaviors are classified and their robustness is further explored, implying that the fast oscillation behavior is more robust than the slow behavior. In addition, bifurcation analysis and landscape approach are employed to study stochastic dynamics and global stability of the circuit oscillations, revealing the possible switching strategies among different behaviors. Taken together, our study provides a natural and physical bases for understanding the occurrence of oscillations in the necroptotic network, advancing our knowledge of oscillations in regulating the various cell death signaling.